2015
DOI: 10.21548/36-1-950
|View full text |Cite
|
Sign up to set email alerts
|

The Sublethal Effects of a Systemic Insecticide on the Vine Mealybug Parasitoids Anagyrus sp. near pseudococci (Girault) and Coccidoxenoides perminutus (Timberlake) (Hymenoptera: Encyrtidae)

Abstract: Imidacloprid is a systemic insecticide used for the control of the vine mealybug Planococcus ficus. However, biological control of P. ficus is the primary alternate management method recommended for the integrated control of this pest. We therefore aimed to establish the detrimental effects on the development of Anagyrus. sp. near pseudococci and Coccidoxenoides perminutus feeding on imidacloprid-contaminated vine mealybugs as indicated by the subsequent emergence and survival of the F 1 generation. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…near pseudococci and Coccidoxenoides perminutus (Timberlake) (Hymenoptera: Encyrtidae) failed to emerge from vine mealybugs contaminated with high doses of imidacloprid. The same experiments also showed that survival of C. perminutus was significantly affected when it was allowed to feed on imidacloprid-contaminated vine mealybugs (Mgocheki and Addison 2015).…”
Section: Side Effects On Natural Enemiesmentioning
confidence: 77%
“…near pseudococci and Coccidoxenoides perminutus (Timberlake) (Hymenoptera: Encyrtidae) failed to emerge from vine mealybugs contaminated with high doses of imidacloprid. The same experiments also showed that survival of C. perminutus was significantly affected when it was allowed to feed on imidacloprid-contaminated vine mealybugs (Mgocheki and Addison 2015).…”
Section: Side Effects On Natural Enemiesmentioning
confidence: 77%
“…see Desneux et al 2007), notably Anagyrus pseudococci (Girault), Anagyrus vladimiri Triapitsyn [ex Anagyrus sp. near pseudococci (Girault)], Coccidoxenoides perminutus Girault (Hymenoptera: Encyrtidae) and the mealybug destroyer, Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae) (Mansour et al 2011a;Planes et al 2013;Mgocheki and Addison 2015). Moreover, the non-rational and excessive use of pesticides may result in environmental pollution.…”
Section: Introductionmentioning
confidence: 99%